Students' Perceptions of the Artificial Intelligence Jenni AI Implementation in Improving Argument Writing Skills - Dewi, Radeni Sukma Indra; Kusumaningrum, Shirly Rizki; Pristiani, Riska; Anggraini, Ade Eka; Effendi, Muhammad Idris; Nugraha, Jaka (Indonesian Research Journal in Education |IRJE|, 2024)
This study explores students' perceptions of using Jenni AI to improve their ability to write scientific arguments in English classes. Involving 67 students as respondents, this study used a quantitative survey method through Google Forms to collect data related to students' experiences and views on the advantages and disadvantages of Jenni AI. The results showed that most students felt significant benefits from Jenni AI, especially in helping to develop stronger arguments, improve writing structure, and overcome writing obstacles such as writer's block. On the other hand, there were concerns about potential negative impacts, such as over-reliance on technology that could inhibit critical thinking and creativity and the risk of unintentional plagiarism. The findings reflect that while AI can enhance the writing process, its use needs to be balanced with an awareness of the risks involved. The implications of this study emphasize a balanced approach to AI in education, as well as the need for learning strategies that optimally integrate technology without compromising students' independence of thought.